Effects of Self-Directed Summary of Performance on Postsecondary Education Students’ Participation in Person-Centered Planning Meetings - Mazzotti, Valerie L.; Kelley, Kelly R.; Coco, Cassie M. (The Journal of special education, 2015)
Teaching students to develop and use a Summary of Performance (SOP) may be one method for teaching self-advocacy skills to ensure students with intellectual disability can advocate for accommodations and supports during Person-Centered Planning (PCP) meetings and in postschool employment settings. This study used a multiple-probe across participants design to investigate the effects of the Self-Directed Summary of Performance (SD-SOP) on participation in PCP meetings for students with intellectual disability. Results indicated increased participation during PCP meetings for all participants. In addition, participants were able to generalize use of the SD-SOP to employment settings. Implications for future research and practice are discussed.